2017
DOI: 10.1111/cup.12885
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous extranodal NK/T‐cell lymphoma mimicking cellulitis an HIV positive patient without lymphopenia

Abstract: We present the case of a 28-year-old male with a history of human immunodeficiency virus (HIV) with a 1-month history of a steadily enlarging, firm painful lesion on the right posterior shoulder. The patient was initially treated for cellulitis given his clinical picture. Histopathologic examination revealed an angiocentric and dermal proliferation of markedly atypical lymphoid cells with numerous mitoses and apoptotic bodies along with broad zones of necrosis. Biopsy revealed the presentation to be consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Only a limited number of case reports and case series have described cutaneous lymphoma in sub‐Saharan Africa, however, there have been no systematic reviews of the clinical and histological findings of cutaneous lymphoma within this population . Several issues, including HIV coinfection, lack of access to specialty providers, and a relatively large dispersed rural population, may contribute to burden and late presentation of disease that can be seen in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of case reports and case series have described cutaneous lymphoma in sub‐Saharan Africa, however, there have been no systematic reviews of the clinical and histological findings of cutaneous lymphoma within this population . Several issues, including HIV coinfection, lack of access to specialty providers, and a relatively large dispersed rural population, may contribute to burden and late presentation of disease that can be seen in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Several other cases of cutaneous ENKTL-NT mimicking infectious skin conditions have been reported (Table I). [3][4][5] In each case, the patients' underlying medical conditions and the frequency at which the favored diagnoses occurred in the general population led to initial misdiagnoses. However, these cases also illustrate the importance of comprehensive work-up when initial therapy is ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…NK/T-cell lymphoma is almost universally associated with Epstein Barr Virus (EBV). [ 2 ] The most common clinical features of cutaneous extranodal NK/T cell lymphoma were subcutaneous multiple nodules confluent and diffused followed by ulcerative lesions, fever, and splenomegaly. The distribution of the lesions was predominantly on the extremities and trunk, especially the lower extremities.…”
mentioning
confidence: 99%
“…[ 5 ] Although CD8 is negative in most cases, a recent study demonstrated that CD8 was found to be positive in 20% cases of ENKTL. [ 2 ] The most common laboratory findings were hyperferritinemia, thrombocytopenia, hypertriglyceridemia, severe anemia, hypofibrinogenemia, and neutropenia,[ 3 ] according to the literature, blood, and bone marrow involvement were not found in many ENKTL cases. [ 6 ]…”
mentioning
confidence: 99%